2015
DOI: 10.31768/2312-8852.2015.37(2):89-93
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Association of Different Types of Leukemias With Radiation Exposure

Abstract: Exposure to ionizing radiation is associated with increasing risk of various types of hematological malignancies. The results of major studies on association of leukemias and radiation exposure of large populations in Japan and in Ukraine are analyzed. The patterns of different types of leukemia in 295 Chernobyl clean-up workers diagnosed according to the criteria of up-to-date World Health Organization classification within 10–25 years following Chernobyl catastrophe are summarized. In fact, a broad spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Through the study on the exposed persons of Hiroshima atomic bomb explosion in Japan and the cleanup personnel of chernobyl nuclear explosion accident, it was found that the incidence of leukemia increased with the increase in the exposure dose, among which the top 3 incidence rates were acute lymphocytic leukemia, acute myeloid leukemia, and chronic myelogenous leukemia. 17…”
Section: Discussionmentioning
confidence: 99%
“…Through the study on the exposed persons of Hiroshima atomic bomb explosion in Japan and the cleanup personnel of chernobyl nuclear explosion accident, it was found that the incidence of leukemia increased with the increase in the exposure dose, among which the top 3 incidence rates were acute lymphocytic leukemia, acute myeloid leukemia, and chronic myelogenous leukemia. 17…”
Section: Discussionmentioning
confidence: 99%
“…Причины развития ММ окончательно не выяснены. Среди возможных этиологических факторов -генетическая предрасположенность, длительная стимуляция иммунной системы при частых инфекциях, аутоиммунных и аллергических заболеваниях, контакт с химическими мутагенами (асбест, инсектициды) и воздействие ионизирующего излучения [9,10]. В частности, выявлено статистически значимое превышение уровня заболеваемости ММ в когорте украинских ликвидаторов последствий аварии на Чернобыльской атомной электростанции по сравнению со спонтанным популяционным уровнем для мужского населения Украины (стандартизованное отношение заболеваемости 1,61; 95 % доверительный интервал 1,01-2,21) [10].…”
Section: Introductionunclassified